Comparison of microscopic and metagenomic approaches to identify cereal pathogens and track fungal spore release in the field - Pilo, Paola; Lawless, Colleen; Tiley, Anna M. M.; Karki, Sujit J.; Burke, James I.; Feechan, Angela (Frontiers in Plant Science, 2022)
Wheat is one of the main staple food crops, and 775 million tonnes of wheat were produced worldwide in 2022 (FAO, 2022). Fungal diseases such as Fusarium head blight, Septoria tritici blotch, spot blotch, tan spot, stripe rust, leaf rust, and powdery mildew cause serious yield losses in wheat and can impact quality (Simón et al., 2021). We aimed to investigate the incidence of spores from major fungal pathogens of cereals in the field by comparing microscopic and metagenomic based approaches for spore identification. Spore traps were set up in four geographically distinct UK wheat fields (Carnoustie, Angus; Bishop Burton, Yorkshire; Swindon, Wiltshire; and Lenham, Kent). Six major cereal fungal pathogen genera (Alternaria spp., Blumeria graminis, Cladosporium spp., Fusarium spp., Puccinia spp., and Zymoseptoria spp.) were found using these techniques at all sites. Using metagenomic and BLAST analysis, 150 cereal pathogen species (33 different genera) were recorded on the spore trap tapes. The metagenomic BLAST analysis showed a higher accuracy in terms of species-specific identification than the taxonomic tool software Kraken2 or microscopic analysis. Microscopic data from the spore traps was subsequently correlated with weather data to examine the conditions which promote ascospore release of Fusarium spp. and Zymoseptoria spp. This revealed that Zymoseptoria spp. and Fusarium spp. ascospore release show a positive correlation with relative humidity (%RH). Whereas air temperature (°C) negatively affects Zymoseptoria spp. ascospore release.